A Molecular Mechanism Study to Reveal Hirudin's Downregulation to PI3K/AKT Signaling Pathway through Decreasing PDGFRβ in Renal Fibrosis Treatment. (7th September 2022) - Li, Ying; Zhang, Ling; Xiong, Weijian; Gao, Xuan; Xiong, Yanying; Sun, Wei
Abstract : Chronic kidney disease (CKD) is identified as a widespread chronic progressive disease jeopardizing public health which characterized by gradually loss of renal function. However, there is no efficient therapy to prevail over this disease. Our study was attempting to reveal hirudin's regulation to renal fibrosis as well as the molecular mechanism. We built renal fibrosis models on both cell and animal levels, which were subsequently given with hirudin disposal; then, we performed the transwell assay to estimate the cells' migration and had our detection to relevant proteins with western blot and immunofluorescence. Finally, we commenced both the identification and the determination to the hirudin targeted proteins and its downstream signaling pathways with the methods of network pharmacology. And the results turned out that when it was compared with the model group, the group with hirudin addition came with the suppression in the migration of renal tubular epithelial cells NRK-52E and with a conspicuous decline in the expressions of fibronectin, N-cadherin, vimentin, TGF- β, and snail. After that, we predicted that there were 17 hirudin target points mainly involving in the PI3K-AKT signaling pathway. Our outcomes of the animal level demonstrated that the conditions of interstitial fibrosis, severe tubular dilatation or atrophy, inflammatory cell infiltration, and massive accumulation of interstitial collagen in the model group were withdrawn after the addition of hirudin. In addition, p-PDGFR β, p-PI3K, and p-AKT protein expressions were significantly reduced, and the PI3K/AKT pathway was downregulated after hirudin treatment in the model group of NRK-52E cells and animals. Therefore, we had our conclusion that hirudin is capable of suppressing the PI3K-AKT signaling pathway as well as the EMT by decreasing PDGFR β phosphorylation.